The Configurations of Personal ldentity in Phenomenology - Walton, Roberto J. (1992)
This paper attempts to show first that the various interpretations of personal identity afforded by recent trends in phenomenology can be assembled into two distinctive groups. On the one hand, a description has been provided of movements, structures or orders into which supposedly subjectivity is dispersed or decentered (J. Patocka, H. Rombach, B. Waldenfels). On the other, it s contended that subjetivity develops on the ground of an original emotional dimension or as a reply to the requirement of responsibility for others (M. Henry, E. Levinas, P. Ricoeur). Second, the article tries to make clear that the post-Husserlian phenornenologies cannot elude the primary sense of identity which Husserl has designated with the name of ego-pole in order to highlight within the monad a centering and unity moment by which "the ego itself is existent for itself in continous evidence" (Hua. l, 100). This means that the ego is aware of itself in a radical an peculiar way invariably involved in all experience. This analysis further suggests that Husserl anticipates positions of the second trend when he inquires back into an undifferentiated primary horizon or discloses a mode of empathy which evades objectivation.